PENGARUH QUICK RATIO, INVENTORY TURNOVER, DAN DEBT TO EQUITY RATIO TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2012 - 2014: PENGARUH QUICK RATIO, INVENTORY TURNOVER, DAN DEBT TO EQUITY RATIO TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2012 - 2014 - Sitepu, Wilsa Road Betterment (JURNAL MUTIARA AKUNTANSI, 2017)
The increase in quick ratio is not always followed by an increase in return on assets. The increase in inventory turnover is not always followed by an increase in return on assets. An increase in debt to equity ratio is not always followed by an increase in return on assets. Based on the identification of the problem of the study is formulated as the followings: Do quick ratio, inventory turnover, and the debt to equity affect the return on assets on food and beverage companies listed on the Indonesia Stock Exchange in 2012-2014 period. This research used a quantitative approach. This type of research is quantitative descriptive. The nature of this research is explanatory. The population of this study were food and beverage companies listed on the Indonesia Stock Exchange in 2012-2014 period. Samples were food and beverage companies that published the complete financial reports in Indonesia Stock Exchange in 2012-2014. Data sources of this research is secondary data from www.idx.co.id. The study councludes that quick ratio and the debt to equity ratio does not affect the return on assets, inventory turnover has a significant negative effect on return on assets. Quick ratio, inventory turnover, and the debt to equity ratio simultaneously have a significant negative effect on return on assets in the food and beverage companies listed on the Indonesia Stock Exchange in 2012-2014 period.Keywords: Quick Ratio, Inventory Turnover, Debt to Equity Ratio. Return on Assets.